Translation of a story into Chilean Sign Language: productions by deaf co-teachers - Morales Acosta, Gina Viviana; Lattapiat Navarro, Pamela (Frontiers in Education, 2024)
Introduction The incorporation of narratives in Chilean Sign Language enriches classroom practices, preserving and transmitting Deaf culture. However, that within the Chilean educational context, the narratives used for instructing Deaf students are translations from written Spanish. This study aims to describe and analyze the narrative structure and the use of Highly Iconic Structures in these translations conducted by Deaf co-teachers into Chilean Sign Language. Method The research adopts a qualitative approach and a descriptive case study design, involving two deaf teachers from an Inclusive Education Program in a school. The data analyzed focus on the video-recorded LSCh translations of the short story “The Greedy Squirrel”. Manual annotations were made on the corpus gloss transcription to first segment by narrative structure for description and then to identify the transfer operations. Results The co-teachers make variations to the narrative structure of the translated text and incorporate specific visual-gestural elements such as the change of narrator to first person; the 45% of the translation is composed of transfer operations. Discussion These findings suggest that the variations in structure and the new visual-gestural information provided by the co-teachers reflect their understanding and use of sign language narrative norms for translation. The use of transfer operations enhances the storytelling experience, although it cannot be conclusively stated how and why teachers decide to use them in translation. The results are limited, as they require comparison with other corpora on translations from written Spanish to LSCh and software-assisted analysis to standardize data, which implies further research on the topic. For now, it is essential that the time allocated to the preparation of educational materials in LSCh be more extensive and better planned.